2013
DOI: 10.1111/fog.12016
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of primary productivity on continental shelves: evidence from maximum size of extant surfclam (Spisula solidissima) populations

Abstract: Atlantic surfclams (Spisula solidissima), among the largest extant non‐symbiotic clam species in the world, live in dense aggregations along the Middle Atlantic Bight (MAB) continental shelf. The food resources that support these populations are poorly understood. An individual‐based model that simulates the growth of post‐settlement surfclams was used to investigate the quantity of food needed to maintain existing surfclam populations along the MAB continental shelf. Food inputs to the model were based on mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 60 publications
(114 reference statements)
1
65
0
Order By: Relevance
“…Munroe et al (2016) found that the maximum size had, in fact, declined for much of the stock since 1980. Simulation modeling of Atlantic surfclam population dynamics shows that this outcome can be derived solely from rising bottom water temperatures (Munroe et al, 2013, although a change in food supply would result in the same outcome. Along the Mid-Atlantic coast, the Atlantic surfclam has supported a fishery since the 1960s that reached total revenues of $29 million in 2011 (Weinberg, 1999; Weinberg et al 5 ; NEFSC 2 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Munroe et al (2016) found that the maximum size had, in fact, declined for much of the stock since 1980. Simulation modeling of Atlantic surfclam population dynamics shows that this outcome can be derived solely from rising bottom water temperatures (Munroe et al, 2013, although a change in food supply would result in the same outcome. Along the Mid-Atlantic coast, the Atlantic surfclam has supported a fishery since the 1960s that reached total revenues of $29 million in 2011 (Weinberg, 1999; Weinberg et al 5 ; NEFSC 2 ).…”
mentioning
confidence: 99%
“…An additional survey conducted in 2004 (Weinberg et al 5 ) confirmed the northward and offshore shift in the Atlantic surfclam stock. One result of these mortality events was the redistribution of the stock north: namely an increasing abundance off the coast of Long Island, New York; the expansion of the population on Georges Bank; and the movement of the seaward boundary of the southern portion of the stock offshore in response to increased bottom water temperatures (Weinberg, 2005;Munroe et al, 2013; NEFSC 2 ). Simulations by Narváez et al (2015) based on stock assessment data from the Northeast Fisheries Science Center and bottom temperature time series obtained through implementation of the Regional Ocean Modeling System for the northwestern Atlantic indicated that episodic warm years caused elevated mortality events in older and larger clams and that these events have occurred with increasing frequency over the last several decades of the 20 th century.…”
mentioning
confidence: 99%
See 3 more Smart Citations